2008
DOI: 10.1534/genetics.108.089805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of thePi-taGene Resistant to Rice Blast in Wild Rice (Oryza rufipogon)

Abstract: Rice blast disease resistance to the fungal pathogen Magnaporthe grisea is triggered by a physical interaction between the protein products of the host R (resistance) gene, Pi-ta, and the pathogen Avr (avirulence) gene, AVR-pita. The genotype variation and resistant/susceptible phenotype at the Pi-ta locus of wild rice (Oryza rufipogon), the ancestor of cultivated rice (O. sativa), was surveyed in 36 locations worldwide to study the molecular evolution and functional adaptation of the Pi-ta gene. The low nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 58 publications
2
69
0
2
Order By: Relevance
“…Pi-ta has been effectively deployed in the United States and around the globe for controlling blast disease Jia et al 2000;Jia 2003;Jia et al 2004a,b;Huang et al 2008;Jia and Martin 2008;Wang et al 2008;Jia et al 2009a). Pi-ta encodes a predicted cytoplasmic protein with a centrally located NBS and a highly interrupted LRR domain (referred to as the LRD) at the carboxyl terminus that recognizes the corresponding avirulence gene AVR-Pita, triggering race-specific resistance.…”
Section: P Lant Resistance (R) Genes Have Evolved To Fightmentioning
confidence: 99%
See 1 more Smart Citation
“…Pi-ta has been effectively deployed in the United States and around the globe for controlling blast disease Jia et al 2000;Jia 2003;Jia et al 2004a,b;Huang et al 2008;Jia and Martin 2008;Wang et al 2008;Jia et al 2009a). Pi-ta encodes a predicted cytoplasmic protein with a centrally located NBS and a highly interrupted LRR domain (referred to as the LRD) at the carboxyl terminus that recognizes the corresponding avirulence gene AVR-Pita, triggering race-specific resistance.…”
Section: P Lant Resistance (R) Genes Have Evolved To Fightmentioning
confidence: 99%
“…A single amino acid substitution, serine (Ser) to alanine (Ala) at the position of 918, in the LRD of the Pi-ta protein was demonstrated to determine the direct interaction with AVR-Pita and the resistance specificity to blast pathogen M. oryazae Jia et al 2000). The resistant Pi-ta allele (Ala-918) was found in O. sativa and its ancestor O. rufipogon ( Jia et al 2004b;Huang et al 2008). Surveys of Pi-ta nucleotide sequences with limited accessions of Oryza species have revealed that the degree of nucleotide diversity is higher at the intron of the Pi-ta gene Huang et al 2008;Wang et al 2008;Yoshida and Miyashita 2009).…”
Section: P Lant Resistance (R) Genes Have Evolved To Fightmentioning
confidence: 99%
“…Because of its facile nature, this approach is being used extensively to identify alleles of agriculturally important traits. Allele mining for blast resistance in rice has been reported from both wild and cultivated species Geng et al 2008;Huang et al 2008). An extensive study of the Pi-ta locus was reported from wild species of rice , cultivated (AA) and wild species (Lee et al 2009), and invasive weedy rice (Lee et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported that O. rufipogon has resilience to blast disease. O. rufipogon has been classified as a promising species that has either the Pi-ta or the Pi-b allele (Eizenga et al, 2009), and some studies have found that the Pi-ta gene in O. rufipogon is similar to that of O. sativa but significantly different from other O. rufipogon genes (Huang et al, 2008). Successful introgression of broad-spectrum blast resistance gene(s) into cultivated rice (O. sativa ssp indica) from O. rufipogon has been reported (Ram et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Geographic distribution surveys of O. rufipogon conducted by the International Rice Research Institute demonstrated that O. rufipogon accession from Malaysia (OR22) exhibited resistance to blast disease (Huang et al, 2008). Gene flow from cultivated rice also occurs, which can persist in wild rice populations, change its genetic composition, and affect the population genetics of wild rice (Ngu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%